Open Statement by [124] Canadian Scholars on Unionization and the Economic and Social Well-Being of Canadians - Albo, Gregory (Just Labour: A Canadian Journal of Work and Society, 2009)
...Americans will decide whether the changes proposed in the Employee Free Choice Act are sensible and positive for their economy and their labour market. But we wish to express our judgment regarding the impact of unionization and collective bargaining on Canadian labour market and social outcomes. In our view, that impact has been generally positive. --From conclusion